Atrial Fibrillation Patients Categorized as “Not for Anticoagulation” According to the 2014 Canadian Cardiovascular Society Algorithm Are Not “Low Risk” - Lip, Gregory Y.H.; Nielsen, Peter Brønnum; Skjøth, Flemming; Rasmussen, Lars Hvilsted; Larsen, Torben Bjerregaard (Canadian journal of cardiology, 2015)
Oral anticoagulation (OAC) is highly effective for stroke prevention in nonvalvular atrial fibrillation. We explored rates of stroke/thromboembolism/transient ischemic attack among the “OAC not recommended” patient group defined according to the 2014 Canadian Cardiovascular Society (CCS) algorithm (based on the Congestive Heart Failure, Hypertension, Age, Diabetes, Stroke/Transient Ischemic Attack [CHADS2] score) who would have been offered OAC using the European Society of Cardiology (ESC) guidelines approach (based on the Congestive Heart Failure, Hypertension, Age [≥75 years], Diabetes, Stroke/Transient Ischemic Attack, Vascular Disease, Age [65-74 years], Sex [Female]; CHA2DS2-VASc score). We identified 22,582 nonanticoagulated patients age < 65 years with a CHADS2 score of 0 who were stratified according to the CHA2DS2-VASc score, except female sex, which would be an indication for OAC according to the ESC guidelines. Event rates for each risk strata were compared using Cox proportional hazard ratios. The overall rate of the combined end point of ischemic stroke/systemic embolism/transient ischemic attack was 4.32 per 100 person-years (95% confidence interval [CI], 3.26-5.74) at 1 year, among the patients who would have had an indication for OAC therapy according to ESC guidelines and “OAC not recommended” according to CCS algorithm. This corresponded to an adjusted hazard ratio of 3.08 (95% CI, 2.21-4.29) relative to the subgroup with no indication for OAC according to the ESC guidelines. A subgroup of patients with previous vascular disease and CHADS2 score of 0 (ie, recommended only aspirin treatment according to the CCS algorithm) had an event rate of 4.84 (95% CI, 3.53-6.62) per 100 person-years at 1-year follow-up. Based on the 2014 CCS algorithm, the “OAC not recommended” subgroup can have a high 1-year stroke rate overall, showing that such patients are not “low risk.” Use of the ESC guideline approach (based on the CHA2DS2-VASc) offers refinement of stroke risk stratification in such patients. L’anticoagulothérapie orale (ACO) est très efficace pour la prévention de l’accident vasculaire cérébral lors de fibrillation auriculaire non valvulaire. Nous avons examiné les taux d’accidents vasculaires cérébraux, de thromboembolies et d’ischémies cérébrales transitoires (ICT) d’un groupe de patients chez lesquels l’ACO n’est pas recommandée telle que définie par l’algorithme de la Société canadienne de cardiologie (SCC; selon le score CHADS2 [Congestive Heart Failure, Hypertension, Age, Diabetes, Stroke/Transient Ischemic Attack : insuffisance cardiaque congestive, hypertension, âge, diabète, accident vasculaire cérébral/ischémie cérébrale transitoire]), mais serait offerte selon l’approche des lignes directrices de la Société Européenne de Cardiologie (SEC; selon le score CHA2DS2-VASc [Congestive Heart Failure, Hypertension, Age (≥ 75 years), Diabetes, Stroke/Transient Ischemic Attack, Vascular Disease, Age (65-74 years), Sex (Female); insuffisance cardiaque congestive, hypertension, âge (≥ 75 ans), diabète, accident vasculaire cérébral/ischémie cérébrale transitoire, maladie vasculaire, âge (65-75 ans), sexe (féminin)]). Nous avons relevé 22 582 patients < 65 ans n’ayant pas reçu d’anticoagulothérapie pour un score CHADS2 de 0 qui, s’ils avaient été stratifiés selon le score CHA2DS2-VASc (excepté le sexe féminin), auraient présenté une indication à l’ACO selon les lignes directrices de la SEC. Les taux d’événements de chaque strate de risque ont été comparés aux rapports de risque proportionnels de Cox. Le taux général des critères d’évaluation combinés de l’accident vasculaire cérébral ischémique/embolie systémique/ICT a été de 4,32 pour 100 années-personnes (intervalle de confiance [IC] à 95 %, 3,26-5,74) après 1 an chez les patients qui auraient présenté une indication à l’ACO selon les lignes directrices de la SEC, mais pour lesquels l’ACO n’était pas recommandée selon l’algorithme de la SCC. Ceci a correspondu à un rapport de risque ajusté de 3,08 (IC à 95 %, 2,21-4,29) relativement au sous-groupe ne présentant pas d’indication d’ACO selon les lignes directrices de la SEC. Un sous-groupe de patients ayant des antécédents de maladie vasculaire et un score CHADS2 de 0 (c.-à-d. que selon l’algorithme de la SCC seul le traitement par aspirine est recommandé) ont eu un taux d’événement de 4,84 (IC à 95 %, 3,53-6,62) pour 100 années-personnes au suivi après 1 an. Selon l’algorithme de la SCC de 2014, le sous-groupe chez qui l’anticoagulothérapie n’est pas recommandée peut avoir un taux général élevé d’accidents vasculaires cérébraux à 1 an, qui montre que ces patients ne sont pas exposés à un risque faible. L’utilisation de l’approche des lignes directrices de la SEC (selon le score CHA2DS2-VASc) permet d’améliorer la stratification du risque d’accident vasculaire cérébral chez ces patients.